2020
DOI: 10.1177/2397002220907389
|View full text |Cite
|
Sign up to set email alerts
|

Leaders—watch out for LMX differentiation: A multilevel model of leader-related antecedences and consequences of LMX differentiation

Abstract: Research has shown that leader–member exchange differentiation affects individual and group outcomes. However, it is not yet clear how such unequal treatment affects the team’s perception of their leader in terms of leader-related outcomes, such as perceived leader communication quality, satisfaction with the leader, and perceived leader effectiveness. We analyzed how leader–member exchange differentiation in teams affects leader-related outcomes, and how it is affected by transformational leadership at the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Third, the results of our study showed that LMX differentiation has cross-level effects on members’ outcomes (COCD and CODD). Although many researchers have emphasized that LMX differentiation is a complex, multifaceted phenomenon whose essence can only be understood when examining it from multiple levels (e.g., Henderson et al, 2008 ; Anand et al, 2011 ), a large number of previous research has been confined to the group level ( Yammarino et al, 2005 ; Anand et al, 2011 ; Harris et al, 2014 ), with the notable exception of the use of multilevel frameworks by some studies ( Estel et al, 2019 ; Choi et al, 2020 ; Eichenseer et al, 2020 ). Our paper helps create more comprehensive predictions about LMX differentiation outcomes by being one of a few studies empirically testing from a multilevel perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the results of our study showed that LMX differentiation has cross-level effects on members’ outcomes (COCD and CODD). Although many researchers have emphasized that LMX differentiation is a complex, multifaceted phenomenon whose essence can only be understood when examining it from multiple levels (e.g., Henderson et al, 2008 ; Anand et al, 2011 ), a large number of previous research has been confined to the group level ( Yammarino et al, 2005 ; Anand et al, 2011 ; Harris et al, 2014 ), with the notable exception of the use of multilevel frameworks by some studies ( Estel et al, 2019 ; Choi et al, 2020 ; Eichenseer et al, 2020 ). Our paper helps create more comprehensive predictions about LMX differentiation outcomes by being one of a few studies empirically testing from a multilevel perspective.…”
Section: Discussionmentioning
confidence: 99%
“…If the differentiation is high, it can have negative consequences (Sloan, 2012). While an understanding of differentiation in a social context is established in the leadership literature (cf Eichenseer et al , 2020; Henderson et al , 2009; Manata, 2020; Park et al , 2022), differentiation has appeared in the justice literature only recently (He et al , 2017; Matta et al , 2020). Moreover, leadership literature has mixed findings with positive and negative consequences (Afshan et al , 2022b; Buengeler et al , 2021).…”
Section: Introductionmentioning
confidence: 99%